HOUSING WITH SUPPORTIVE SOCIAL SERVICES AND HOSPITAL USE. (11th November 2018) - Gusmano, M K; Rodwin, V G; Weisz, D
Abstract: Can housing with supportive social services affect the use of hospitals? We compare hospital use among Medicare beneficiaries living in a housing program for older people, and other Medicare beneficiaries 65 years and over, living in the same neighborhoods. We find that Medicare beneficiaries living in housing with supportive social services are less likely to be hospitalized, have shorter lengths of stay in the hospital, and have lower rates of hospital discharge for ambulatory care sensitive conditions (ACSC), than their counterparts living in the same neighborhoods. Even after controlling for age, gender, race and ethnicity, the odds of being hospitalized for ACSC are about 44 percent lower among residents of housing with supportive social services than among their counterparts. Our findings suggest that increased investment in upstream, social determinants of health can reduce rates of hospital use for conditions that could be managed in an ambulatory setting.